Alzheimer’s Biomarkers are Correlated with Brain Connectivity in Older Adults Differentially during Resting and Task States - Jiang, Yang; Huang, Haiqing; Abner, Erin; Broster, Lucas S.; Jicha, Gregory A.; Schmitt, Frederick A.; Kryscio, Richard; Andersen, Anders; Powell, David; Van Eldik, Linda; Gold, Brian T.; Nelson, Peter T.; et al. (Frontiers in Aging Neuroscience, 2016)
ß-amyloid (Aß) plaques and tau-related neurodegeneration are pathologic hallmarks of Alzheimer’s disease (AD). The utility of AD biomarkers, including those measured in cerebrospinal fluid (CSF), in predicting future AD risk and cognitive decline is still being refined. Here we explored potential relationships between functional connectivity patterns within the default-mode network (DMN), age, CSF biomarkers (Aß42 and pTau181) and cognitive status in older adults. Multiple measures of functional connectivity were explored including a novel time series based measure (Total Interdependence; TI). In our sample of 27 cognitively normal older adults, no significant associations were found between levels of Aß42 or pTau181 and cognitive scores or regional brain volumes. However, we observed several novel relationships between these biomarkers and measures of functional connectivity in DMN during both resting-state and a short-term memory task. First, increased connectivity between bilateral anterior middle temporal gyri was associated with higher levels of CSF Aβ42 and Aβ42/pTau181 ratio (reflecting lower AD risk) during both rest and task. Second, increased bilateral parietal connectivity during the short-term memory task, but not during rest, was associated with higher levels of CSF pTau181 (reflecting higher AD risk). Third, increased connectivity between left middle temporal and left parietal cortices during the active task was associated with decreased global cognitive status but not CSF biomarkers. Lastly, we found that our new TI method was more sensitive to the CSF Aβ42-connectivity relationship whereas the traditional cross-correlation method was more sensitive to levels of CSF pTau181 and cognitive status. With further refinement, resting-state connectivity and task-driven connectivity measures hold promise as non-invasive neuroimaging markers of Aβ and pTau burden in cognitively normal older adults.